Cultural differences in the provision of social assistance - Pastrňák, René (Univerzita Pardubice, 2010)
This text is devoted to cultural and ethnic differences, which in direct interaction of social support affect the quality of care in both residential and the outpatient social services. The aim of the text is to highlight the possibility of conflicts resulting from low cultural sensitivity, which is usually characterized by a reluctance to learn, to empathy and to deal new approaches with the client. It is essential to change the status quo and prepare for the future, aware of the worker's professional competence, the need to learn and be under the cross-cultural supervision.
Keywords: cultural differences; global world; social support; intercultural empathy; conflict; communication